Politics in the Making of HIV/AIDS in South Africa - Pienaar, Kiran (2016)
The HIV epidemic remains one of the most challenging of modern times, despite the enormous promise of anti-retroviral treatment. This timely book takes a critical look at HIV/AIDS in the context of South Africa, the country with the largest HIV epidemic in the world. Drawing on feminist science and technology studies and a close analysis of a range of textual sources, Politics in the Making of HIV/AIDS in South Africa tracks how the disease has been formed and transformed through political struggles. It illuminates the ways these struggles have also generated new selves for those living with HIV. In conducting this enquiry, the book addresses pressing questions about the politics of public health, the ethics of biological citizenship, and agency and the making of neoliberal subjects. It should appeal to scholars and students with interests in the sociology of health and medicine, the body in society, science and technology studies, and public health.